Pengembangan Program Mobile Library untuk Meningkatkan Kualitas Pembelajaran Al-Qur'an di Masyarakat Pedesaan - Arafik Syaif (GUYUB: Journal of Community Engagement, 2026)
ow Qur’anic literacy in rural communities of East Nusa Tenggara (NTT) remains a critical issue that threatens the continuity of Qur’anic learning across generations. Remote geographical conditions, a shortage of qualified instructors, limited religious education facilities, and restricted access to learning resources hinder the ability of community members to read and understand the Qur’an. Without effective intervention, these challenges may weaken the quality of religious education and community religious life. Therefore, a sustainable and context-based empowerment model is needed to improve access to Qur’anic learning in remote areas.  This community service program aimed to enhance Qur’anic literacy and strengthen the capacity of local leaders to sustain learning activities independently. The program was implemented in three villages in East Solor District, NTT, using a Service Learning approach with a mixed-methods design. Participants included 31 community leaders, consisting of 6 mosque imams and 25 Qur’an teachers, along with residents from the three target villages. Data were collected through observations, in-depth interviews, focus group discussions, and structured questionnaires. The intervention was conducted over 12 weeks with three sessions per week using age-appropriate learning methods and locally contextualized teaching materials.  The results showed a significant improvement in Qur’anic literacy, with an average increase of 31.66%. The program also generated sustainable impacts, reflected in the commitment of 93.55% of community leaders to continue the initiative independently and the establishment of Qur’anic learning groups in each village. These findings confirm the effectiveness of a community empowerment-based Mobile Library model in improving Qur’anic literacy in remote rural areas